From ancestral wisdom to ethical living: indigenous parenting and moral formation in children - Habibat Bolanle Abdulkareem; Kamoru Abidoye Tiamiyu; Jamila Yusuf (Universitas Pendidikan Indonesia, 2025)
In an increasingly globalized world, the preservation of cultural heritage remains crucial in maintaining an ethical and moral foundation. Consequently, character education needs to be implemented in parenting. This study examines the significance of indigenous parenting approaches, specifically their role in promoting ethical development in children. Through a comprehensive literature review and case studies from various indigenous communities, the research highlights how storytelling, communal living, rites of passage, and traditional guidance systems serve as tools for ethical education. The research examines the interaction between these practices and the challenges of contemporary society, advocating for a balanced integration of indigenous and modern parenting strategies. The findings underscore the importance of maintaining cultural roots to ensure the transmission of ethical principles to future generations, ultimately contributing to the holistic development of children and the sustainability of cultural identity. In its findings, the study highlights the crucial role of cultural preservation in fostering ethically grounded future generations. In conclusion, Indigenous parenting, if respected and integrated into education and society, will strengthen children's moral character and help preserve cultural identity and generational wisdom. Abstrak Dalam dunia yang semakin mengglobal, pelestarian warisan budaya tetap penting dalam memelihara landasan etika dan moral pada anak-anak sehingga pendidikan karakter perlu diterapkan dalam pola pengasuhan. Studi ini mengeksplorasi pentingnya pendekatan pengasuhan adat, dengan fokus pada peran mereka dalam membina perkembangan etika pada anak-anak. Melalui tinjauan literatur dan studi kasus yang komprehensif dari berbagai komunitas adat, penelitian ini menyoroti bagaimana mendongeng, kehidupan komunal, ritus peralihan, dan sistem bimbingan tradisional berfungsi sebagai alat untuk pendidikan etika. Penelitian ini meneliti interaksi antara praktik-praktik ini dan tantangan masyarakat kontemporer, yang menganjurkan integrasi yang seimbang antara strategi pengasuhan adat dan modern. Temuan-temuan tersebut menggarisbawahi pentingnya menjaga akar budaya untuk memastikan transmisi prinsip-prinsip etika kepada generasi mendatang, yang pada akhirnya berkontribusi pada perkembangan holistik anak-anak dan keberlanjutan identitas budaya. Dalam temuannya, penelitian ini menekankan peran penting pelestarian budaya dalam memelihara generasi mendatang yang berlandaskan etika. Kesimpulannya, pola asuh masyarakat Pribumi, jika dihormati dan diintegrasikan ke dalam pendidikan dan masyarakat, akan memperkuat karakter moral anak dan membantu melestarikan identitas budaya serta kearifan generasi. Kata Kunci: adat; akar budaya; anak-anak; pendidikan karakter; praktik pengasuhan